2021
DOI: 10.1021/acsbiomaterials.1c00008
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Nanoscale Erythrocyte Delivery System for Enhancing Chemotherapy via Overcoming Biological Barriers

Abstract: Overcoming multiple biological barriers, including circulation time in vivo, tumor vascular endothelium, reticuloendothelial system (RES), extracellular matrix (ECM), etc., is the key to improve the therapeutic efficacy of drug delivery systems in treating tumors. Inspired by the ability of natural erythrocytes to cross multiple barriers, in this study, a biomimetic delivery system named NE@DOX-Ang2 was developed for enhancing the chemotherapy of breast cancer, which employed nano-erythrocyte (NE) encapsulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“… Alimoradi et al (2018 ) developed a stable nitric oxide (NO)-releasing nanoparticle (polystyrene-maleic acid [SMA]-tert-dodecane S-nitrosothiol [tDodSNO]) to enhance the anticancer properties of doxorubicin (Dox) and overcome the biologic barriers of in vitro and in vivo studies. As delivery systems and nanomedicine platforms, the dual-functionalized graphene oxide (GO)-based nanocarrier, the Salmonella enterica serovar Typhimurium, multifunctional hybrid NPs, PEG-PLGA NPs coated with hyaluronic acid, and biomimetic nanoscale erythrocyte could overcome biological barriers to enhance tumour responses to chemotherapy in BC treatment ( Suh et al, 2019 ; Cristofolini et al, 2020 ; Almoustafa et al, 2021 ; Liu et al, 2021b ; Zhang et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“… Alimoradi et al (2018 ) developed a stable nitric oxide (NO)-releasing nanoparticle (polystyrene-maleic acid [SMA]-tert-dodecane S-nitrosothiol [tDodSNO]) to enhance the anticancer properties of doxorubicin (Dox) and overcome the biologic barriers of in vitro and in vivo studies. As delivery systems and nanomedicine platforms, the dual-functionalized graphene oxide (GO)-based nanocarrier, the Salmonella enterica serovar Typhimurium, multifunctional hybrid NPs, PEG-PLGA NPs coated with hyaluronic acid, and biomimetic nanoscale erythrocyte could overcome biological barriers to enhance tumour responses to chemotherapy in BC treatment ( Suh et al, 2019 ; Cristofolini et al, 2020 ; Almoustafa et al, 2021 ; Liu et al, 2021b ; Zhang et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…From confocal microscopy, we can demonstrated that the loaded drugs can extravasate via the tumor vessel and penetrate deeply into the tumor [74]. Simple methods, like shear force, can get nanoscale vesicles [41,79,80]. The nano RDVs have intact membrane proteins and glycolipids, exhibiting better stability than single liposomes.…”
Section: Rbc-derived Vesicles In Delivery Systemmentioning
confidence: 99%
“…[ 1,153 ] The EM‐NVs have been utilized to directly encapsulate chemotherapy drugs, enzymes, proteins, polysaccharides, toxins, and genetic material. [ 154–157 ] The camouflaged synthetic NPs included polymer NPs (e.g., PLGA, liposomes), [ 156,158 ] metal NPs (e.g., gold, Fe 3 O 4 , hollow copper sulfide), [ 41,159 ] inorganic non‐metal NPs (e.g., mesoporous SiO 2 ), [ 160 ] albumin NPs (e.g., BSA), and nanogels. [ 30,161 ] It is noteworthy that there are little target ligands on the EM‐NVs to provide the navigation for cargoes to locate at the disease region.…”
Section: Biomedical Applications Of Erythrocyte‐inspired Materialsmentioning
confidence: 99%